The Effect of Club Social Responsibility on Customer Citizenship Behavior with the Mediating Role of Brand Equity - Mohammad sahebkaran; Seyedeh Azra Mirkazemi; Atefeh Sadat Mostafavi (Research in Sport Management and Marketing, 2024)
Purpose: The purpose of this research was to investigate the role of the social responsibility of clubs on customer citizenship behavior through the mediation of brand value.Method: The method of this research is a descriptive survey and the statistical population of this research is all the customers of South Khorasan fitness clubs. Due to the uncertainty of their exact number, the method of 5 to 15 times the number of questionnaire items was used to determine the sample size. After collecting the questionnaires (370 questionnaires), 340 questionnaires were analyzed. The instruments of this research included three questionnaires: the social responsibility questionnaire by Bakhshandeh et al. (2015), the citizenship behavior questionnaire by Gruth (2005) and the special brand value questionnaire by Azimzadeh and Mohammadi (2015). To analyze the data and the relationships between the variables, Spss24 and Amos24 software were used.Results: The results showed that there is a significant relationship between the social responsibility of fitness clubs the citizenship behavior of customers (r=0.598) and brand value (r=0.777). Also, there is a significant relationship between brand equity and customer citizenship behavior (r=0.870). Finally, the results showed that the social responsibility of clubs has a positive and significant effect on customer citizenship behavior through the mediation of the brand equity variable (r=0.630).Conclusion: In light of the research's conclusions, managers of sports clubs can make significant progress in appealing to citizens by developing and putting into practice social responsibility and branding plans that foster positive customer relations on all fronts.